Life cycle assessment of land-based greenhouse gas removal technologies. - Lefebvre, David (Cranfield University, 2021)
Greenhouse gas removal technologies (GGRT) are needed to meet the UNFCCC aim to limit the global average temperature increase to 2°C above pre-industrial levels. GGRTs vary in carbon sequestration potential, readiness level, scalability, cost, required surrounding environment and related environmental and social effects. Quantifying these components in every context is critical to ensure maximum greenhouse gas removal efficiency while minimising negative effects. In this thesis I use life cycle assessment (LCA) to assess the carbon sequestration potential of three GGRTs: enhanced weathering, biochar and reforestation. I use case studies in São Paulo, Brazil for biochar and enhanced weathering, and in the Peruvian Amazon for reforestation. In addition, I use LCA to identify the most important processes in each system and to determine context-specific limits that switch the systems from net GHG sequestration to net GHG emission. Overall, this work promotes the use of LCA to consider GGRTs in their entirety and predict their context-specific carbon capture potential, along with their limitations and potential caveats to guide both the science and policy communities. This thesis was made possible thanks to funding through the SOILS-R-GGREAT (NE/P019498/1) project of the greenhouse gas removal (GGR) program. The GGR program is financed by the UK Natural Environment Research Council (NERC), Engineering and Physical Science Research Council (EPSRC), Economic and Social Science Research Council (ESRC) and the UK department for Business, Energy and Industrial Strategy (BEIS).
PhD in Environment and Agrifood
Keywords: LCA; GGRT; CDR; NET; enhanced weathering; biochar; reforestation